Risk factors associated with comorbid asthma in patients with chronic rhinosinusitis with nasal polyps: a cross-sectional study - Fangyuan Li; Xuechen Wang; Shen Shen; Kai Huang; Ming Wang; Xiaofang Liu; Chengshuo Wang; Jianmin Jin; Luo Zhang (BMC Pulmonary Medicine, 2022)
Abstract Background Although 20–60% of patients with chronic rhinosinusitis with nasal polyps (CRSwNP) have asthma, the risk factors associated with comorbid asthma are not clear. The aim of the study was to investigate the factors associated with asthma, and develop a practical scoring system to screen asthma comorbidity in CRSwNP patients. Methods This report describes a cross-sectional study with consecutive CRSwNP patients. Two cohorts of CRSwNP patients named “modelling” group and “validation” group were investigated respectively. Logistic regression analysis was performed based on demographic and clinical data collected from patients in the modelling group to determine the risk factors associated with asthma, and establish a scoring system for screening comorbid asthma. Receiver operating characteristic curve was constructed to evaluate the screening system; the optimal cut-off point was established by means of the Yoden Index. The consistency between the diagnosis of asthma by the Global Initiative for Asthma (GINA) criteria and by the screening system was assessed by Kappa value in the validation group. Results Totally 150 patients in modelling group and 78 patients in validation group were enrolled. Female gender (odds ratio [OR] = 6.4; P < 0.001), allergic rhinitis (OR = 2.9; P = 0.021), serum total (T)-immunoglobulin (Ig) E ≥ 69.0kU/L (OR = 12.0; P < 0.001), and blood eosinophil count  ≥ 0.35 × 109/L (OR = 4.0; P = 0.001) were shown to be independent risk factors for asthma in patients with CRSwNP. Based on these variables, a scoring system (FAIE) ranging from 0(no risk) to 6(high risk); was developed. The area under the receiver operating characteristic curve of the system was 0.823, and the optimal cut-off value was 3 points, with sensitivity 83.8% and specificity 68.6% for screening asthma. The asthma comorbidity determined with FAIE score ≥ 3 points in the validation group, was moderately consistent with that defined by GINA (Kappa = 0.513, P < 0.001), with sensitivity 76.9% and specificity 74.4%. Conclusions Female gender, allergic rhinitis, serum T-IgE level, and blood eosinophil count are independent risk factors for asthma comorbidity in patients with CRSwNP, and the FAIE system may be practical for screening comorbid asthma in these patients.